Recovering the local volatility in Black-Scholes model by numerical differentiation - Yin, Binbin; Ye, Yuzhang (Applicable analysis, 2006)
In this article, a numerical method for recovering the local volatility in Black-Scholes model is proposed based on the Dupire formula in which the numerical derivatives are used. By Tikhonov regularization, a new numerical differentiation method in two-dimensional (2-D) case is presented. The convergent analysis and numerical examples are also given. It shows that our method is efficient and stable.